2014
DOI: 10.1371/journal.pmed.1001768
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Versus Mobile Clinic HIV Testing and Counseling in Rural Lesotho: A Cluster-Randomized Trial

Abstract: Niklaus Labhardt and colleagues investigate how different HIV testing and counseling strategies, based on home visits or mobile clinics, reach different populations in a rural African setting. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
133
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(146 citation statements)
references
References 37 publications
10
133
3
Order By: Relevance
“…The percentage of testers who were young adults testers <age 25 or <30 years) was reported in 17 home HTC studies 5,18,2931,35,37,38,45,63,64,6870,73,74,90,117 , one home with self-testing 11 , 13 mobile 10,12,13,68,91,93,9597,103,107,114 , two index partner 48,88 , two campaign 47,77 , 20 facility VCT 12,51,52,54,64,88,89,9193,95,104107,114,118120 , and six facility PITC 58,82,86,88,110,113 . Results varied considerably by study (Supplementary Figures S29–S35).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The percentage of testers who were young adults testers <age 25 or <30 years) was reported in 17 home HTC studies 5,18,2931,35,37,38,45,63,64,6870,73,74,90,117 , one home with self-testing 11 , 13 mobile 10,12,13,68,91,93,9597,103,107,114 , two index partner 48,88 , two campaign 47,77 , 20 facility VCT 12,51,52,54,64,88,89,9193,95,104107,114,118120 , and six facility PITC 58,82,86,88,110,113 . Results varied considerably by study (Supplementary Figures S29–S35).…”
Section: Resultsmentioning
confidence: 98%
“…Uptake was reported in 31 home HTC studies 5,14,15,18,27,2938,40–45,53,6274 , two home with self-testing 11,75 , two mobile 10,68 , three index partner or family member 4850 , four campaign 46,47,76,77 , three workplace 7880 , three facility VCT 54,56,81 , and 11 facility PITC studies 56,57,59,60,8187 . Overall, community modalities had high uptake (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… b The formula for number of new HIV infections is a function of 2 additional HIV transmission parameters: (1) the β parameter (0.098) represents the average number of transmissions per person per year resulting from PLHIV without suppressed viral load and was consistently estimated from the other parameters in the incidence formula; (2) the ϕ parameter represents the percentage reduction in infectivity among people with suppressed virus and was estimated conservatively as 0.98, given that no linked infections were observed in index participants whose HIV infections were stably suppressed by ART in the HIV Prevention Trials Network 052 trial [28]. …”
Section: Resultsmentioning
confidence: 99%
“…Some countries in SSA, like Malawi, South Africa and Zambia, have integrated HIV testing within community campaigns that provide screening or prevention services for diseases other than HIV [8]. HPTN 043, a community-randomised trial showed increased rates of HIV testing amongst 16 to 32 years old and detected 3.6 times as many HIV-positive clients with community-based HCT when compared to standard clinic-based HCT [41]. Another recent community randomised trial from Lesotho confirmed these trends, finding higher uptake of HCT during home-based testing when compared to HCT conducted at health facilities and that home-based testing was better for accessing men [42].…”
Section: Innovative Strategies For Universal Test and Treatmentioning
confidence: 99%